Exploring character strengths among South African university students: Insights from a WhatsApp-based intervention - Anita Campbell; Sean Paul Abrahams (Journal of Student Affairs in Africa)
Character strengths, such as resilience, justice, and appreciation of beauty, play a key role in student well-being and academic engagement. This study explores the strengths profiles of 302 students at a South African university and evaluates the effectiveness of a six-week WhatsApp-based intervention designed to enhance self-awareness and strengths application. Using the VIA Character Strengths Survey, we found Kindness, Love of Learning and Fairness were the most highly endorsed strengths, while Zest, Bravery and Self-regulation were lowest. Daily reflective prompts encouraged students to apply their strengths in different contexts. Post-intervention survey results from 55 participants indicated that most found the course beneficial for increasing self-awareness (90%) and understanding how to apply their character strengths in daily life (87%). Additionally, 93% of respondents reported that the daily messages helped them understand how to use their strengths to achieve their goals. Findings are discussed in relation to South Africa’s social and cultural landscape, highlighting the potential of low-cost, digital interventions to support student development. While limited to a single institution, this study suggests promise for culturally responsive, strengths-based courses in higher education.